Developing a Self-Respect Inventory Based on Islamic Sources - Maryam Heidari; Mohammad Masoud Diyarian; Mohammad Reza Abedi (مطالعات اسلام و روانشناسی, 2021)
This study was conducted in order to construct a list of self-esteem based on Islamic sources. The current study is descriptive-analytical and survey method. To do that, first, the necessary sources were studied and investigated according to Islamic sources in order to extract the attributes related to self-esteem. Then, a 90-item questionnaire was prepared, which was examined by Islamic and psychological experts, and finally 55 items remained, which were administered in the form of a survey study on a sample of 216 university students in Khomeini Shahr. The reliability of the self-esteem checklist was calculated and confirmed by three methods: "internal consistency (with Cronbach's alpha 0.89), retest 0.74 and halving 0.869. Validity of self-esteem checklist with three methods: Content validity review (with the opinion of twelve religious and psychological experts and calculation of CVR coefficient), criterion validity (positive and significant correlation of 0.73 self-esteem checklist with standard Borba moral intelligence questionnaire) and structural validity (factor analysis and factor model analysis) were examined in the sample and good results were obtained. Finally, standard T scores were calculated and a norm table was prepared for the self-esteem list. The results of this evaluation show that the list of self-esteem has desirable psychometric properties to measure the level of self-esteem in individuals based on Islamic sources.